Wethouder van Duyn arriveert voor het slaan van de eerstepaal van Hollandia Autowrakken B.V. Amsterdam
Wethouder van Duyn arriveert voor het slaan van de eerstepaal van Hollandia Autowrakken B.V. Amsterdam.